Impact of milk feeding frequency on performance, health and behaviour of crossbred cattle calves - HAJAM, JAVID REHMAN; GAUR, G K; DUTTA, NARAYAN; BHARTI, P K; SINGH, MUKESH; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2018)
The present study was undertaken to study the impact of milk feeding frequency on performance, health and behaviour of crossbred cattle calves. A total of 12 crossbred (Vrindavani) calves were allocated equally in to two groups viz. control (G-I) and experimental group (G-II). During the experimental period (from16th to 70th day of birth), the calves in Gr-II and G-I group were fed milk once and twice daily, respectively without any change in total offered milk quantity. The mean birth weight (kg) of calves in control and experimental group were 21.01±0.88 and 21.25±0.88 kg, respectively. The total body weight gain of calves in control and experimental group were 21.06±0.39 and 21.08±0.39 kg, respectively. The average weekly body weights, gains and body measurements in general were non-significantly different in control and G-II group from 1st to 10th week of age. However, the body length was significantly (P<0.05) higher in G-II from third week to end of experiment. As a whole, 16.67% calves in G-I and 33.34% calves in G-II suffered from calf scour. The change in feeding schedule had no significant effect on immune status and behavioral activities of calves. Once daily feeding saved 29.41% (36 man minutes) labour than twice daily feeding schedule. It was concluded that reduction in milk feeding frequency to calves did not affect growth, feed intake, health, behaviour and overall performance, hence one time milk feeding to calves may be adopted at organized herds, where weaning is being practiced, in view of saving labor cost.